2022
DOI: 10.1155/2022/6596028
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of ZrO2‐CeO2 Hybrid Nanofluid and Response Surface Methodology for the Prediction of Heat Transfer Performance: The New Correlations

Abstract: This article experimentally and statistically reports the convective heat transfer performance of a cylindrical mesh-type heat pipe apparatus filled with ZrO2-CeO2/water-ethylene glycol nanofluids. In this regard, ZrO2-CeO2 nanoparticles were synthesized and characterized through the Scanning Electron Microscope and Powder X-ray diffraction methods followed by the preparation of hybrid ZrO2-CeO2 nanofluids of various concentrations ranging from 0.025 to 0.1%. The heat transfer features of a tubular heat pipe w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Because of their high thermal conductivity and low viscosity, hybrid nanofluids may have an impact on heat transfer systems. 54,55 Declaration of conflicting interests…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their high thermal conductivity and low viscosity, hybrid nanofluids may have an impact on heat transfer systems. 54,55 Declaration of conflicting interests…”
Section: Discussionmentioning
confidence: 99%
“…To plot contour, sensitivity outcomes and tables, the response surface method is employed. 55 Coding for factors is used.…”
Section: Response Surface Methods (Rsm)mentioning
confidence: 99%
“…Many similar studies with addition of nanoparticle in a base fluid were shown to enhance the overall heat transfer (e.g. addition of Copper [17], TiO2 and ZnO [18], MgO -TiO2, ZrO2 -CeO2 [19,20], graphene [21,22] in a base fluid Ethylene Glycol-Water mixture).…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing such hybrid nanofluids, various preliminary studies have produced amazing results. For example, Vidhya et al [18] found that hybrid nanofluids have excellent thermal performance potential and are particularly suitable for heat transfer applications. Rajesh et al [19] analyzed the energy augmentation by using hybrid nanofluid in an infinite vertical plate with ramped wall temperature.…”
Section: Introductionmentioning
confidence: 99%